Neurobiology of Sleep Disturbances in PTSD Patients and Traumatized Controls: MRI and SPECT Findings - Nardo, Davide; Högberg, Göran; Jonsson, Cathrine; Jacobsson, Hans; Hällström, Tore; Pagani, Marco (Frontiers in Psychiatry, 2015)
Objective: Sleep disturbances such as insomnia and nightmares are core components of Post-Traumatic Stress Disorder (PTSD), yet their neurobiological relationship is still largely unknown. We investigated brain alterations related to sleep disturbances in PTSD patients and controls by using both structural and functional neuroimaging techniques. Method: Thirty-nine subjects either developing (n=21) or not developing (n=18) PTSD underwent MRI and a symptom-provocation protocol followed by the injection of 99mTc-HMPAO. Subjects were also tested with diagnostic and self-rating scales, on the basis of which a Sleep Disturbances Score (SDS; i.e., amount of insomnia/nightmares) was computed. Results: Correlations between SDS and grey matter volume (GMV)/regional cerebral blood flow (rCBF) were computed in the whole sample, and separately in the PTSD and control groups. In the whole sample, higher sleep disturbances were associated with significantly reduced GMV in amygdala, hippocampus, anterior cingulate, and insula; increased rCBF in midbrain, precuneus and insula; and decreased rCBF in anterior cingulate. This pattern was substantially confirmed in the PTSD group, but not in controls. Conclusion: Sleep disturbances are associated with GMV loss in anterior limbic/paralimbic, PTSD-sensitive structures, and with functional alterations in regions implicated in REM-sleep control, supporting the existence of a link between PTSD and sleep disturbance.